2022
DOI: 10.3389/fphys.2022.885183
|View full text |Cite
|
Sign up to set email alerts
|

Search for Venous Endothelial Biomarkers Heralding Venous Thromboembolism in Space: A Qualitative Systematic Review of Terrestrial Studies

Abstract: Background: The recent discovery of a venous thrombosis in the internal jugular vein of an astronaut has highlighted the need to predict the risk of venous thromboembolism in otherwise healthy individuals (VTE) in space. Virchow’s triad defines the three classic risk factors for VTE: blood stasis, hypercoagulability, and endothelial disruption/dysfunction. Among these risk factors, venous endothelial disruption/dysfunction remains incompletely understood, making it difficult to accurately predict risk, set up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“… In spaceflight, the diagnostic accuracy of terrestrial US criteria is unknown. Slow, stagnant, retrograde blood flow, especially in the IJV, due to volume overload and elevated venous pressures secondary to the classic cephalic fluid shift 8 , 56 , 65 , may mimic the aspects encountered in venous thrombosis. It is important to improve V-US scanning conditions by decreasing central venous pressure and venous congestion through the effect of venous interventions such as thigh cuffs, LBNP, Mueller manoeuvres and contralateral IJV compression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… In spaceflight, the diagnostic accuracy of terrestrial US criteria is unknown. Slow, stagnant, retrograde blood flow, especially in the IJV, due to volume overload and elevated venous pressures secondary to the classic cephalic fluid shift 8 , 56 , 65 , may mimic the aspects encountered in venous thrombosis. It is important to improve V-US scanning conditions by decreasing central venous pressure and venous congestion through the effect of venous interventions such as thigh cuffs, LBNP, Mueller manoeuvres and contralateral IJV compression.…”
Section: Discussionmentioning
confidence: 99%
“…The third issue is the lack of studies on diagnostic accuracy and diagnostic management in patients with clinically suspected DVT in space. Therefore, the optimal venous ultrasound (V-US) criteria to rule-out and conversely rule-in the diagnosis of DVT in space remain to be defined, as is the case with clinical presentation including VTE risk factors 7 , and D-dimer and endothelial biomarkers 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Hemodynamic assessments of LBNP application in previous studies have been largely carried out non-invasively [ 6 ], commonly using pulse wave forms or Doppler probes, and therefore limiting their mechanistic accuracy. Furthermore, in human studies the occurrence of syncope due to reduced cerebral perfusion has been reported frequently [ 18 , 19 ]. However, the impact of hazardous low systemic pressures (MAP < 30 mmHg) on ventricular function and mechano-energetics remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Over the course the topical team's tenure, we have published on the likelihood of flow abnormalities in contributing to VT formation 12 , endothelial disruption related risks of VT 46 , and diagnostic modalities for VT in space (in review). We found that current tools on board the ISS are insufficient to characterize blood flow patterns that may contribute to clot formation and that there are no validated biomarkers that reliably predict increased likelihood of VT formation in otherwise healthy people.…”
Section: Gap Analysis and Recommendationsmentioning
confidence: 99%
“…We do not have a valid spaceflight compatible imaging diagnosis pathway.Determination of a gold-standard diagnostic algorithm/pathway (biomarkers and imaging). This involves progressing existing work on diagnostic methods (U/S and biomarkers) for VT during spaceflight46 . The ultrasound criteria to rule-out and rule-in the diagnosis of VT in spaceflight must be established.…”
mentioning
confidence: 99%